Numerical simulation and experimental study of medium and deep ground source heat pump system in a cold and arid region - Hongwei Feng; Hui Xu; Hongtu Feng; Ying Gao (Case Studies in Thermal Engineering)
Although medium and deep ground source heat pump system are more advantageous for heating compared to other heat pump systems in winter, there has been limited researches on medium and deep ground source heat pump system in a cold and arid region. In order to study the heating performance of the system and address heating issues in a cold and arid region, the experimental tests were conducted from November 1, 2021, to March 31, 2022, and the results showed that the heating system operates stably, maintaining indoor heating above 18 °C throughout the day. The average coefficient of performance (COP) is 5.67, and the cumulative power consumption is 185971 kWh. Additionally, this study established a new three-dimensional numerical model of a medium and deep borehole heat exchanger (MDBHE) and validated it with experimental test results. The numerical simulation analyzed the impact of different insulation layers, well diameters, flow rate and well depths on the heat pump performance and heating effectiveness. This experimental research and numerical simulation are significant to promote the development of low-carbon as soon as possible.